The Effect Of Workload, Burnout And Resilience On Worker Overall Performance At PT. Financial Institution Rakyat Indonesia, East Flores Waiwerang Unit - Olivia Sintia Tokan; Siti Mujanah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This take a look at studies discuss the effect of workload,burnout and resilience on worker overall performance at PT. financial institution Rakyat Indonesia, East Flores Waiwerang Unit. The studies targets to be done are realize and analyze workload, burnout, and resilience partially or concurrently on worker overall performance at PT. finacial institution Rakyat Indonesia, East Flores Waiwerang Unit. This studies makes use of sampling statistics as many as 50 human beings at PT. financial institution Rakyat Indonesia Unit Wawierang East Flores through dispensing questionnaires the use of quantitative statistics sort. Inside the studies consequences, the T test indicates that the variables Workload and Resilience have a nice or enormous effect on Worker Performance. The Burnout variable has a negativeor no enermous impact on worker performance. And the outcomes of the F test display that the variables Workload, Burnout and Resilience concurrently have an effect on worker overall Performance at PT. financial institution Rakyat Indonesia, East Flores Waiwerang Unit.